Results of a Single Arm Pilot Study of a Mobile Messaging Intervention for Hookah Tobacco Cessation in Young Adults - Mays, Darren (Tob Use Insights, 2020)
BACKGROUND: Hookah tobacco use is common among young adults. Unlike cigarette smoking, there is limited evidence on mobile (ie, mHealth) interventions to promote cessation. OBJECTIVES: This pilot study tested the preliminary effects of mobile messaging for cessation in young adult hookah smokers. METHODS: Young adults (N = 20) aged 18 to 30 years who smoke hookah at least monthly and have done so at least once in the past 30 days received a 6-week mHealth multimedia messaging (text and images) intervention. Message scheduling (2 days/week × 6 weeks) was based on the literature. Content was developed iteratively by the study team and focused on health harms and addictiveness of hookah. Content was individually tailored by baseline hookah use frequency, risk beliefs, and responses to interactive text messages assessing participants’ hookah tobacco use behavior and beliefs to maximize impact. Engagement was assessed during the intervention, and we examined effects on risk perceptions, risk beliefs, and risk appraisals, motivation to quit, and behavior change immediately post-intervention. RESULTS: Participants responded to 11.5 (SD = 0.69) of 12 text message prompts on average, endorsed high message receptivity (M = 6.1, SD = 0.93, range = 1-7), and reported the messages were helpful (M = 8.5, SD = 1.5, range = 1-10). There were significant (P < .05) increases in risk perceptions (d’s = 0.22-0.88), risk appraisals (d = 0.49), risk beliefs (d = 1.11), and motivation to quit (d = 0.97) post-intervention. Half of participants reported reducing frequency of hookah use (20%) or quitting completely (30%) by end of treatment. CONCLUSIONS: These pilot results provide preliminary support for an mHealth messaging intervention about risks of hookah tobacco for promoting cessation. Rigorously examining the efficacy of this promising intervention is warranted.